Sex Differences in Stroke Recovery - Sue-Min Lai, PhD, MS, MBA; Pamela W. Duncan, PhD; Paul Dew, MD, MPH; John Keighley, MS (Centers for Disease Control and Prevention, 2005)
Introduction This study examined differences between men and women in the ability to perform basic activities of daily living, instrumental activities of daily living, and higher physical functioning after stroke. The objective of the study was to determine whether sex differences in stroke recovery can be explained by depressive status beyond older age, stroke severity, prestroke physical functioning, and other medical comorbidities. Methods A total of 459 stroke patients were recruited from acute and subacute facilities in an urban midwestern community. These patients were followed prospectively from stroke onset until 6 months poststroke. All study participants were assessed using standardized stroke outcome measures, including the National Institutes of Health Stroke Scale, the Barthel Activities of Daily Living Index, the Lawton Instrumental Activities of Daily Living scale, and the SF-36 Health Survey physical functioning scale. The Geriatric Depression Scale was used to assess depressive status. Each outcome was measured at baseline (within 2 weeks of stroke onset), as well as 1, 3, and 6 months poststroke. Prestroke physical functioning, stroke characteristics, and comorbidities were also assessed at baseline. Results Female patients in the study were older than male patients, with a mean age of 71 years for women vs 69 years for men. Female patients reported lower prestroke physical functioning than their male counterparts. Six months after stroke, women in the study were less likely than the men to achieve a score of ≥95 on the Barthel Activities of Daily Living Index (hazards ratio [HR] = 0.68; 95% confidence interval [CI], 0.52-0.90), carry out eight of nine instrumental activities of daily living without assistance (HR = 0.46; 95% CI, 0.30-0.68), and score ≥90 on the SF-36 Health Survey physical functioning scale (HR = 0.54; 95% CI, 0.28-1.01). When age, prestroke physical functioning, stroke severity, and depressive status at baseline were controlled in the analysis, women in the study continued to be less likely (HR = 0.51; 95% CI, 0.32-0.79) than men in the study to be able to carry out eight of nine instrumental activities of daily living completely without assistance, but there were no observed sex differences in achievement of independence in basic activities of daily living or higher physical functioning. Conclusion Prestroke physical functioning and depressive symptoms are important factors in the investigation of sex differences in stroke recovery. Lower recovery of activities of daily living and physical functioning in women after stroke may be due to multifactorial effects of older age, poor physical function prior to stroke onset, and depressive status after stroke.